"Cosentinia" vellea communities in the Lusitan Duriensean biogeographical sector (Spain-Portugal) - Amich, Francisco; Bernardos, Sonia (Botanica Complutensis, 2013)
We study in this paper the phytosociological behavior of plant communities characterized by the presence of Cosentinia vellea in the Lusitan-Duriensean biogeographical sector. After a detailed analysis of the same, and its comparison with related phytocoenoses, we believe should be included in the association Cheilantho maderensis-Cosentinietum velleae. Finally we analyze and discuss the framework in higher units.
Keywords: Cosentinia communities; Duero River; Iberian Peninsula; Lusitan-Duriensean